The checklist - Woolridge, Addie (Montlake Romance, 2021)
Killing it at work? Check. Gorgeous boyfriend? Check. Ambitions derailed by an insecure boss? Sigh--check. Things were going a little too well for Dylan Delacroix. After upstaging her boss on a big account, she gets dispatched to the last place she wants to be: her hometown, Seattle. There, she must use her superstar corporate-consulting skills to curb the worst impulses of an impossibly eccentric tech CEO--if she doesn't, she's fired. The fun doesn't stop there: Dylan must also negotiate a ceasefire in the endless war between her bohemian parents and the straitlaced neighbors. Adding to the chaos is a wilting relationship with her boyfriend and a blossoming attraction to the neighbors' smoking-hot son. Suddenly Dylan has a million checklists, each a mile long. As personal and professional pressures mount, she finds it harder and harder to stay on track. Having always relied on her ability to manage the world around her, Dylan's going to need a new plan. She may be down, but she's definitely not out.